(untitled) (Biocenosis, 2014)
Reproduction of free living Nurse Shark in shallow waters is very stable in their frequent of observation at Cabo Blanco Reserve, these mean it can be used as a resource management to ensure its conservation and ecotourism as an sustainable alternative if it is done correctly. This paper brings together the key recommendations for an appropriate low impact visitation.